Augmented limb blood flow during neurovascular stress in physically fit women. (27th June 2013) - Dishman, Rod K.; Jackson, Erica M.; Nakamura, Yoshio; Ray, Chester A.
Abstract The study examined whether cardiorespiratory fitness modifies cardiovascular responses by normotensive men and women during the Stroop color‐word interference test. Independent of age and an estimate of body fatness, fitness level was positively related (R2 = .39 and .51) to increases in limb blood flow and vascular conductance, coherent with cardiac‐vagal withdrawal and a decrease in heart period, among women but not men. Fitness was unrelated to changes in systolic and diastolic blood pressures and muscle sympathetic nerve activity. The augmented hemodynamic responses among fitter women were not consistent with passive vasodilation via withdrawal of sympathetic neural tone. The results encourage further gender comparisons testing whether fitness augments limb blood flow during mental stress by neurohumoral and flow‐mediated vasodilatory mechanisms or by increased cardiac output.